Fluvic acid carbon as a dignostic feature for agricultural soil evaluation (Semiárida, 2020)
The fluvic acid fraction in considered to be sensitive to agronomic and environment factors. Therefore, the objectives of this study were to evaluate total carbon (TC) and fluvic acid carbon (FC) contens and to establish a possible relationship between the FC fraction and coarse organic matter in agricultural soils (CTVs), (ii) conservation tilled soils (CSTs), and (iii) virgins soils (VIRs) from a wide region in Argentina. The investigation includes 114 surface samples of Hapludolls, Haplustolls, and Entisols ranging in texture from sand to slit loam. In 29 selected samples, two separate soil mineral fraction were used (